Pediatric Otogenic Sigmoid Sinus Thrombosis: Case Report and Literature Reappraisal - Andrea Scherer MD; Andrew Jea MD (SAGE Publishing, 2017)
The purpose of this study was to review our experience with a single case of mastoiditis associated with sigmoid sinus thrombosis and increased intracranial pressure, and to review the experience of others through prior publications. We reviewed a case of a 6-year-old boy with an acute otitis media and mastoiditis, with associated ipsilateral sigmoid sinus and contralateral distal transverse sinus thrombosis. Based on the literature and our own experience, we conclude that most children with dural sinus thrombosis from acute otitis media and mastoiditis, in the setting of increased intracranial pressure, attain a good neurological outcome with a conservative neurosurgical approach. The mainstay of treatment seems to be appropriate antibiotic coverage and anticoagulation. Surgeries such as external ventricular drain, serial lumbar punctures, intracranial pressure monitor, and endovascular thrombectomy are reserved for patients with neurological deterioration despite maximal medical treatment.